Entrepreneurship Innovations in Tourism - Stojanović, Suzana T (Industrija, 2018)
The paper analyses the effects of entrepreneurial innovations in tourism, with a special emphasis on the possibility for further development of the quality of Vranjska Banja (spa resort) services in order to increase the attendance at this great spa tourism potential in Serbia. The aim of the paper is to determine the factors that will contribute to the greater visitor numbers of Vranjska Banja. The basic research question is: To what extent the content of the tourist offer of Vranjska Banja, the price and quality of the services that are provided contribute to the visit to the specified destination? According to the defined research problem, which is insufficient attendance at Vranjska Banja, the survey of visitors of Vranjska Banja was carried out with specially defined questions adapted to the subject and purpose of the research, by combining the statistical method of samples with the method of interviews and questionnaires. Impact data were analysed using the five-point Likert scale method and the descriptive statistics method. The obtained results indicate that there is a high level of loyalty of visitors who visit Vranjska Banja every year and that they are satisfied with the tourist offer, the quality of services and the price of services, that is, the hypotheses that there is a positive correlation between the visits to Vranjska Banja and the tourist offer, the prices and quality of services have been confirmed. It is necessary to improve the tourist offer in order to increase the number of new visitors.